Firearm Kidney Trauma in Cotonou: Interest of Strict Surveillance in Two Clinical Cases - AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; ATTOLOU, Setondji Gilles Roger; GANDJI, Elohonnan wilfired; MAHAMANE, Salissou Adamou; HODONOU, Fred Detondji; YEVI, Ines Dodji; AGOUNKPE, Mickael Michel; Sossa, Jean; NATCHAGANDE, Gilles; MEHINTO, Kouassi Delphin (My University, 2018)
Kidney trauma is defined as any traumatic lesion that may concern the four components of the kidney: the capsule, the renal parenchyma, the upper urinary excretory pathways and the renal pedicle. Ballistic trauma is the result of the penetration into the body of a projectile: bullet, lead, metallic fragment from the envelope or the contents of an explosive device. Ballistic trauma is rare in the absence of war. Those of the kidney are even rarer in this context. However, their severity is related not only to the weapon used, but also and especially to an injury of the renal pedicle. In this work, we report two cases of kidney trauma by firearm received at the urology department of the national university hospital center of Cotonou, for which we had opted for surveillance.
Keywords: Trauma; ballistics; kidney; surveillance.